AB0678 Peripheral ulcerative keratitis associated to autoimmune systemic diseases: visual prognosis and occurrence while systemic disease in remission. (12th June 2018) - Pelegrin, L.; Hernández-Rodríguez, J.; Torras, J.; Espinosa, G.; Adán, A.; Sainz, M.T.
Abstract : Background: Background: Peripheral ulcerative keratitis (PUK) is a corneal crescent-shaped inflammatory damage with/without concomitant scleritis. PUK can occur isolated or as part of an underlying systemic disease (SD). Objectives: Objective: To characterise a cohort of PUK patients with a long-term follow-up and to evaluate clinical (ocular and systemic) parameters as predictors of ocular prognosis, in terms of relapses and visual outcomes. Methods: Methods: Retrospective review (1996–2017) of patients with PUK from a multidisciplinary Uveitis Unit (Ophthalmology/Autoimmune Diseases). Data recorded included ophthalmological features, clinical assessment and laboratory markers at disease onset, and therapeutic interventions, ocular relapses and visual outcomes during follow-up. Results: Results: Among 18 PUK patients evaluated, 3 were idiopathic, 3 infectious and 12 (67%) associated with systemic diseases (SD-PUK): 8 rheumatoid arthritis (RA), 2 ANCA-vasculitis, 1 SLE and 1 Takayasu's arteritis. Among SD-PUK patients, sex ratio favoured women (rate 9:3) with a median age of 72 (range 33–85) years. Unilateral/bilateral involvement occurred in 7/5 patients and associated scleritis in 50% (11 eyes). All patients presented with eye pain/redness and visual impairment. Four (33%) patients (5 eyes) suffered ocular perforation and required surgery. All patients received topical glucocorticoids (GC), 75% systemic GC, 33% additional immunosuppressant, and 42% biologic therapy. Mean follow-up were 7.3 (range 0.5–12) years. The annual relapse rate was 0.3. Final visual acuity worsened in 42% (8 eyes). In 10 (83%) patients PUK onset occurred previous to SD diagnosis or with SD in remission, and only 3 (25%) were receiving treatment for SD. No prognostic factors were found to correlate with PUK relapses and final visual acuity/ocular perforation. Conclusions: Conclusions: RA and ANCA-vasculitis are the SD more frequently associated with PUK. Visual outcomes are poor in less than 50% of patients despite of topical and systemic GC/biologic therapy. SD-PUK may emerge previous to the SD diagnosis or with the associate SD in remission. Disclosure of Interest: None declared